Making Wise the Stranger: Sapiential Hospitality in Proverbs 1–9 - Ho, Shirley S. (Open theology, 2021)
Jayme Reaves uses Genesis 19:1-14; Joshua 2:1-22; Judges 19:14-27; and the cities of refuge texts in Deuteronomy 4:41-3 and 19:1-10 as biblical sources to conceptualize a so-called "protective hospitality." This article utilizes the book of Proverbs to argue that it reflects the same protective motivations regarding hospitality, with a sapiential twist. Specifically, Proverbs 1-9 depicts two forms of hospitality: sapiential hospitality and pseudo hospitality. Sapiential hospitality protects the stranger from fraudulent hospitality. It is a form of absolute hospitality, meant to avert strangers from falling into the trap of false hospitality offered by organized crime syndicates. Although Lady Wisdom is vulnerable to attack from villainous strangers, she is also resilient enough to make strangers wise and thrive.